‘Standing’ room only: a vintage issue in estate administration claims - Mohd Noor, Nor Azlina; Abd Aziz, Ahmad Shamsul (UUM Press, 2019)
The doctrine of standing or locus standi governs the rule of competency of a person that submits their grievances to the court. A beneficiary, usually an incompetent plaintiff due to the lack of locus standi, is not a qualified litigant to seek the court’s intervention in administering the deceased’s estate. The prevailing legal position in Malaysia is that the estate beneficiaries are not authorized to bring forth any action against any party on behalf of the estate, until a sealed order of the letter of representation has been presented. The fundamental issue in question is whether the doctrine of standing has denied the inherent right of beneficiaries to exploit the deceased’s estate. Hence, in light of this scenario, this paper aims to analyse the tendency of the court on deciding cases that relates to the standing of beneficiaries who are not personal representatives, when they submit claims on behalf of the estate. In this context, this paper uses the content analysis method to analyse past concluded cases and relevant legal provisions. This paper concludes that the Federal Court had whittled down the strict rule that beneficiaries should first obtain the grant of letters of representations for deceased’s estates by providing the locus standi to submit any legal claims on behalf of the estates. Therefore, by allowing the claims made by the beneficiaries, the court has acknowledged the existence of special circumstances that can be applied to exceptional cases.